2010
DOI: 10.1210/jc.2009-2112
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Fasting Plasma Cortisol Is Associated with Ischemic Heart Disease and Its Risk Factors in People with Type 2 Diabetes: The Edinburgh Type 2 Diabetes Study

Abstract: The previously described associations between HPA axis activation and features of the metabolic syndrome are present among people with type 2 diabetes. Elevated plasma cortisol is also associated with a greater prevalence of ischemic heart disease, independent of conventional risk factors. Understanding the role of cortisol in the pathogenesis of ischemic heart disease merits further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
4
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 35 publications
3
73
4
3
Order By: Relevance
“…Fraser et al [27] demonstrated that in general population cortisol excretion rate Results are standardized β coefficients and significance, adjusted R 2 , and significance of model AUC area under the curve *p < 0.05, † p < 0.01, ‡ p < 0.001, § p < 0.0001, ¶ p < 0.00001 did not correlate with blood pressure but correlated strongly with BMI, WHR, and negatively with HDL cholesterol [27]. In The Edinburgh Type 2 Diabetes Study in type 2 diabetic patients, elevated fasting cortisol was associated with ischemic heart disease and its risk factors [28]. We can speculate that hyperinsulinemia and insulin resistance commonly observed in abdominal obesity can increase the HPA axis activity, but when overt type 2 diabetes develops, even without complications, the HPA axis is clearly hyperactive.…”
Section: Discussionmentioning
confidence: 97%
“…Fraser et al [27] demonstrated that in general population cortisol excretion rate Results are standardized β coefficients and significance, adjusted R 2 , and significance of model AUC area under the curve *p < 0.05, † p < 0.01, ‡ p < 0.001, § p < 0.0001, ¶ p < 0.00001 did not correlate with blood pressure but correlated strongly with BMI, WHR, and negatively with HDL cholesterol [27]. In The Edinburgh Type 2 Diabetes Study in type 2 diabetic patients, elevated fasting cortisol was associated with ischemic heart disease and its risk factors [28]. We can speculate that hyperinsulinemia and insulin resistance commonly observed in abdominal obesity can increase the HPA axis activity, but when overt type 2 diabetes develops, even without complications, the HPA axis is clearly hyperactive.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, follow-up of women exposed to extreme stress in pregnancy indicate these women are at increased risk of adverse mental health [121] . In the non-pregnant state, activation of the HPA axis increases the risk of metabolic and psychiatric disease [8,[122][123][124][125][126][127][128][129][130] . Preliminary evidence that altered HPA responses to pregnancy may influence later maternal mental health comes from a small study showing that increased cortisol responses to a standardized psychosocial stress test during healthy pregnancy predict postpartum depressive symptoms [131] .…”
Section: Maternal Consequences Of Stress and Altered Hpa Axis Activitmentioning
confidence: 99%
“…Проблема метаболічних порушень у клініці посідає одне з ведучих місць [1,7,10,12]. Особливо привертає увагу розвиток метаболічного синдрому(МС) при ожирінні, оскільки, як фактор ризику, трапляється в першу чергу при ішемічній ( вінцевій ) хворобі серця, цукровому діабеті і низці інших патологій [4,5,10]. На даний час вивченню патогенезу МС присвячена велика кількість дослі-джень як в експерименті, так і в клініці [2,3,11].…”
Section: львівський національний медичний університет імені данила гаunclassified